Education through e‐learning: Case of Serbia - Marković, Mirjana Radović (Journal of Business Economics and Management, 2009)
The objective of this paper is to analyze education through e‐learning. The author presents an overview of some recent projects with focus on Serbia and uses their results to discuss advantages of using e‐learning as an alternative opportunity and support to “face‐to‐face” education. From the author’s viewpoint, it is believed that online learning will not replace face‐to‐face learning but still should be offered as a style of learning that suits students needs. Through the research done on this subject, it has been identified that online learning can assist in complementing studies when coupled with face‐to‐face learning. In addition, the author’s findings suggest that without good policy and financial support there is no good interaction between e‐learning (classroom learning )or face‐to‐face learning and e‐learning. First Publish Online: 14 Oct 2010